Implementation of Green Open Space Management Policy in Sidoarjo Regency - Sulianti Wahida Astuti; Isnaini Rodiyah (Indonesian Journal of Public Policy Review, 2022)
The results of the research on Implementation of Green Open Space Arrangement Policies in Abhirama Park Pondok Jati Pagerwojo Sidoarjo Regency show that communication indicators, in implementing the green open space arrangement policy in Abhirama Park, information dissemination is carried out through socialization by utilizing existing media such as banners and posters to protect The cleanliness provided around Abhirama Park as well as field officers also conveyed directly about the appeal and field officers were also as sensitive as possible to convey information about green open space, for example protecting the park area environment. However, there are still people who do not obey the appeal because there have been no special sanctions applied to visitors who do not follow the rules. There are 12 people in charge of Green Open Space in Abhirama park, 1 supervisor, 6 park maintenance, 4 people for guarding and 1 canteen guard. With this amount, the park maintenance staff is still lacking because the condition of the park has started to return to normal so that visitors are increasing. But specifically for field supervisors, field coordinators include staff in the office who are responsible for managing green open space in the form of special allowance salaries, while for field officers there is no only contract salary. Bureaucratic structure indicators, SOPs have been running according to the agreed provisions, where the SOPs have explained how to maintain green open spaces to how the process of the policy is.